S25 Sleepy Snorers With "flow Limitation Syndrome": A Missed Opportunity For Cpap?. (10th November 2014) - Yadavilli, R; Chakrabarti, B; McDougall, S; Horne, L; Emegbo, S; Craig, S; Duffy, N; Parker, R; O'Reilly, J
Abstract : Background: The apnoea–hypopnoea index (AHI) is used to define Obstructive Sleep Apnoea Syndrome (OSAS). Some subjects however, present primarily with excessive daytime sleepiness (EDS) and loud snoring, but investigation may reveal an elevated Respiratory Disturbance Index (RDI) with most events comprising Flow limitations. Little UK based data exists regarding treatment outcomes in this group. Methodology/results: 118 subjects (mean age 52 years; Epworth sleepiness scale score (ESS) 13.58 (5.30); 80% male) presented between November 2011–October 2013 to the Sleep Service with EDS as a primary symptom, loud snoring, RDI >15 with AHI≤11 (Mean RDI 21.77 (9.43)); AHI 8.03(2.74); ODI 6.72 (4.49) and were treated with CPAP. At 30 day compliance review, 60% (71/118) had benefited from CPAP with mean ESS pre-CPAP 14.13 (5.12) falling to 7.70 (4.82) following CPAP. The mean BMI was found to be significantly higher in those 71 subjects benefiting from CPAP (33.20 (SD 8.13) v 30.26 (SD 7.40); p = 0.04) but no significant differences were noted in baseline Epworth score, age, gender, AHI, RDI, ODI and Pulse Transit Time (PTT). This "Flow Limitation" cohort was compared with 261 subjects (mean age 56 years; ESS 12.47(5.61); 82%Male) diagnosed with OSAS during the same time period (Mean AHI 37.11 (19.94); mean ODI 31.15 (19.74) and treated with CPAP. 76% (199/261) of the OSAS group reported benefit from CPAP; ESS fell from 13.24 (5.35) to 6.60 (4.74) following CPAP therapy. Comparing the "Flow Limitation" group with the "OSA" group, the mean BMI (32.03(7.94) v 34.70(8.65); p = 0.004) and age (51.75(12.34) v 56.20(12.18); p = 0.001) were significantly lower in the "Flow Limitation" subjects but no significant difference was noted in baseline ESS. Those deriving benefit from CPAP in the OSA group demonstrated significantly higher CPAP usage (4.45(2.24) v 3.83(2.15) hours/night; p = 0.04). Conclusion: Basing treatment decisions on AHI rather than RDI may miss a proportion of patients exhibiting similar levels of EDS as those with OSAS who would otherwise have gained benefit from CPAP. Despite the observed benefit, CPAP usage appeared lower in this "Flow Limitation" cohort who appeared overall to be a younger group with a lower BMI compared to those with OSA.